Historical dictionary of Bangladesh - Rahman, Syedur, Ph.D (Historical dictionaries of Asia, Oceania, and the Middle East ;, 2010)
Bangladesh (literally, the land of the Bengalis) is the most recent addition (in 1971) to the independent nations of South Asia. It had previously been known as East Pakistan, and prior to that it was part of British India. It has been inhabited by peopleof different races and religions and ruled over by different leaders who imposed different regimes. It is overpopulated and underdeveloped, but there is much more to it than that. Bangladesh has a long and oftentimes proud tradition: it has produced writers and artists of genius, and it is an important outpost of Islam. And, with a population.